From Celebrity to Politician: The Indonesian Women Celebrity in House of Representative (DPR RI) 2004-2007 - Nyarwi - (The Indonesian Journal of Communication Studies, 2008)
In the last election 2004 event, there are many Indonesian celebrities who had become a public figure and they have been contesting in the political field. Indonesian women celebrities have been supporting many national political parties as vote getter. One of the greatest trends around the 2004 general election was the commoditization of popularity of Indonesian women celebrities. This paper examines the Indonesian women celebrities’ elected at the 2004 general election. First, it is pertinent to explain the political snap shot of Indonesian celebrity political trends in contemporary Indonesian democracy. Second, the paper explores how the political opportunity of Indonesian women celebrity to obtain legislative power in the House of Representative. Third, the paper explores the commoditization of popularity among the Indonesian women celebrity in the political field. Fourth, the paper explores the development of traditional entertainer, celebrity endorser, and celebrity politic in Indonesia. Fifth, the paper explores how the commoditization and political contestation among Indonesian celebrities in the post-journalism of mass media industries. Finally, it examines the development of popular cultures, political popularity, and political marketing strategy of Indonesian celebrity.